Osteological evidence of butchering technique found in the Neolithic site of Fruntișeni (Vaslui County). (September 2015) - Prociuc, Mariana; Codrea, Vlad
Abstract: The Neolithic site of Fruntișeni (Eastern Romania, Vaslui County) belongs to the Stoicani-Aldeni culture and it is located on an important contact zone between neighbouring Neolithic cultures — Gumelnița, Cucuteni and Petrești. Zooarchaeological evidence concerning this culture is scarce and consists of a small set of data represented by identified taxa from assemblages. In this paper we present the classification of cut marks observed on bone surfaces and their functionality. The bones bearing cut marks belong both to domestic mammals ( Bos taurus, Ovis aries, Capra hircus, Sus domesticus ) and wild mammals ( Bos primigenius, Cervus elaphus, Capreolus capreolus, Sus ferus ). Studying the bone surface modification produced by meat supplying contributes to a better understanding of the managing of carcass dismemberment, issues of nourishment, and knowledge about butchery techniques from that period. When the studied material consists of food garbage, many cut marks are obscured by the high fragmentation ratio. Thus, even without entire skeletons which can show us the exact butchery pattern used, we can still claim as we illustrated in this paper that the butchery pattern can vary between species. This study is the first of this kind for a faunal assemblage from Romania. Highlights: Classification and description of cut marks exhibited on all types of bone, for the first time in Romania The areas of interest for meat production are highlighted. The pattern of butchery practice consists of skinning, head removal and carcass portioning.